2017
DOI: 10.17116/endoskop201723217-22
|View full text |Cite
|
Sign up to set email alerts
|

Videoendosurgical techniques in diagnosis of chest diseases in HIV patients

Abstract: Проведен анализ результатов видеоэндоскопических методов диагностики заболеваний органов грудной клетки у ВИЧинфицированных пациентов. Выполнены следующие видеоэндохирургические и видеоассистированные оперативные вмешательства: видеоторакоскопия, биопсия плевры/легкого/лимфоузла-55 (70,5%); видеомедиастиноскопия, биопсия лимфатических узлов средостения-17 (21,7%); резекция легкого (сегментарная или лобэктомия)-5 (6,5%); пневмонэктомия-1 (1,3%). Из 78 оперированных пациентов диагноз туберкулеза был установлен у… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…showed that chest radiography (CXR) can be used to screen for evidence of subclinical TB, but is insensitive. Mycobacterium tuberculosis (bacteriological and molecular genetic), computed tomography, and, if necessary, invasive diagnostic tests to confirm the diagnosis, which allowed confirming or ruling out active tuberculosis in individuals with a positive Diaskintest and provide the identification of TB patients in the early stages of the disease[47].After the differential diagnosis of tuberculosis and LTBI was carried out in subjects who had a positive Diaskintest reaction, all people with LTBI were prescribed preventive therapy. Since HIV-infected patients with reduced CD4+ counts have an increased proportion of negative test results in the presence of tuberculosis infection, preventive therapy is prescribed when the number of these cells is less than 350[48,49] even in patients with a negative Diaskintest reaction.…”
mentioning
confidence: 99%
“…showed that chest radiography (CXR) can be used to screen for evidence of subclinical TB, but is insensitive. Mycobacterium tuberculosis (bacteriological and molecular genetic), computed tomography, and, if necessary, invasive diagnostic tests to confirm the diagnosis, which allowed confirming or ruling out active tuberculosis in individuals with a positive Diaskintest and provide the identification of TB patients in the early stages of the disease[47].After the differential diagnosis of tuberculosis and LTBI was carried out in subjects who had a positive Diaskintest reaction, all people with LTBI were prescribed preventive therapy. Since HIV-infected patients with reduced CD4+ counts have an increased proportion of negative test results in the presence of tuberculosis infection, preventive therapy is prescribed when the number of these cells is less than 350[48,49] even in patients with a negative Diaskintest reaction.…”
mentioning
confidence: 99%